Assessing the magnitude and lifestyle determinants of food addiction in young adults - Humera Vasgare; Devaki Gokhale; Anuja Phalle; Sammita Jadhav (Eating and Weight Disorders)
Abstract Purpose Food addiction involves excessive consumption of highly processed foods rich in salt, sugar, and fats driven by hedonic eating behaviors. Increased food addiction, especially among young adults, could potentially lead to eating disorders. Hence, the current study aimed to assess the magnitude and lifestyle determinants of food addiction in young adults from Mumbai, India Methods Healthy young adults (n = 354) aged 18–25 years were recruited using convenience sampling. Utilizing web-based platforms, the Yale Food Addiction Scale 2.0 was administered. Statistical analysis was performed with significance at a p value of ≤ 0.05. Results The mean age of participants was (20.99 ± 1.94) years, and the magnitude of food addiction was 11.3%. Sociodemographic determinants such as age (p = 0.000), socio-economic status (p = 0.000), and education (p = 0.000), and lifestyle determinants such as BMI (p = 0.012), dietary habits (p = 0.000), sleep (p = 0.001), physical activity (p = 0.001), anxiety (p = 0.001), and depression (p = 0.000) were significantly associated with food addiction. However, after adjusting for sociodemographic factors, the relationship between lifestyle factors and food addiction became evident. The frequent consumption of specific unhealthy foods increased the risk (OR ≥ 1.0, p value ≤ 0.05), while the consumption of healthy foods reduced the risk (OR<1.0, p value ≤ 0.05) of food addiction. Conclusion The present study revealed a rising magnitude of food addiction and its determinants among Indian youth, highlighting the urgency of sensitization and designing targeted nutrition interventions to combat food-related addiction and hence reducing the risk of eating disorders. Level of Evidence: Level V, Descriptive Study.